2015
DOI: 10.1093/mnras/stv689
|View full text |Cite
|
Sign up to set email alerts
|

The accretion history of dark matter haloes – I. The physical origin of the universal function

Abstract: Understanding the universal accretion history of dark matter halos is the first step towards determining the origin of their structure. We use the extended Press-Schechter formalism to derive the halo mass accretion history from the growth rate of initial density perturbations. We show that the halo mass history is well described by an exponential function of redshift in the high-redshift regime. However, in the lowredshift regime the mass history follows a power law because the growth of density perturbations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
106
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 32 publications
6
106
0
Order By: Relevance
“…We note that the exclusions of objects with masses M halo = 10 7-9 M from our discussion would not have an effect in our conclusions as the CSFRD and SFRF are dominated by more massive haloes (Figs 4 and 6). 6 Correa et al (2015) proposed that the total mass growth rate of a halo can be approximated byṀ tot = 71.6 M yr −1 ( These haloes represent only ∼1 per cent of the total star-forming population at this era. In the local Universe the number of massive haloes M halo ≥ 10 11 M is significantly higher than that of z ∼ 4.…”
Section: T H E C O N T R I B U T I O N O F H a L O E S W I T H D I F mentioning
confidence: 99%
“…We note that the exclusions of objects with masses M halo = 10 7-9 M from our discussion would not have an effect in our conclusions as the CSFRD and SFRF are dominated by more massive haloes (Figs 4 and 6). 6 Correa et al (2015) proposed that the total mass growth rate of a halo can be approximated byṀ tot = 71.6 M yr −1 ( These haloes represent only ∼1 per cent of the total star-forming population at this era. In the local Universe the number of massive haloes M halo ≥ 10 11 M is significantly higher than that of z ∼ 4.…”
Section: T H E C O N T R I B U T I O N O F H a L O E S W I T H D I F mentioning
confidence: 99%
“…For the mass-accretion history of the host, we adopt the analytic EPS model from Ref. [30]. This model provides the mean evolution of a halo that ends up with mass M 0 at z ¼ 0.…”
Section: Semianalytic Modelmentioning
confidence: 99%
“…Clusters found through wide-angle surveys, such as ROSAT (Piffaretti et al 2011), Planck (Planck Collaboration et al 2016, and SPT (Bleem et al 2015), are also shown. For comparison we plot the mass accretion history of halos of different initial masses M in derived with the COncentration-Mass relation and Mass Accretion History code (COMMAH; Correa et al 2015aCorrea et al , 2015bCorrea et al , 2015c with continuous lines 3 Figure 1 shows the cluster masses as a function of redshift for the KCS sample described in this paper (XMM2235, XMM2215, and Cl0332). For reference, we also show the two additional overdensities that are part of the full KCS sample, JKC S041 and RCS2345.…”
mentioning
confidence: 99%
“…We overplot models for the growth of cluster mass with time, based on the COncentration-Mass relation and Mass Accretion History (COMMAH; Correa et al 2015aCorrea et al , 2015bCorrea et al , 2015c code, which uses an analytic model to generate halo mass accretion rates for a variety of redshifts and cluster masses.…”
mentioning
confidence: 99%